Potential of Louhan fish (Amphilophus labiatus) as a local fishery pest in Lake Toba North Sumatra as a source omega 3 and 6 fatty acids - Pandiangan Maruba; Sihombing Dewi Restuana; Daniela Connie; Sibuea Posman; Tampubolon Sanggam Dera Rosa; Sitohang Apul; Sitanggang Lasmianna (BIO Web of Conferences)
Identifying the oil of Louhan fish (Amphilophus labiatus), which are now considered a nuisance and a danger to the native fish of Lake Toba, as a source of omega 3 and omega 6 fatty acids is the aim of the study. From August to November 2023, the research was conducted at the Faculty of Agriculture Laboratory at Santo Thomas Catholic University. The physical and chemical properties of Louhan fish oil, as well as its fatty acid content, were examined using a gas chromatograph. The physical and chemical analysis of Louhan fish oil revealed the following results: turbidity point 36 oC, total solids 34 oBrix, free fatty acid content 3.35 mg KOH/g, peroxide number 7.3 meq/kg, iodine number 45 mg/100g, and saponification number 198 mg KOH/g. The results of the gas chromatography study showed that the levels of unsaturated fatty acids were higher than those of saturated fatty acids. Furthermore, linolenic acid, an omega 3 fatty acid, and linoleic acid, an omega 6 fatty acid, were found in the analysis's results. Louhan fish oil may include omega 3 and omega 6 fatty acids, which are beneficial to human health, based on its fatty acid composition.